Revolution in the Stock Exchange Industry: Two-Sided Platforms, Battle for Liquidity, and Financial Centres. - Wójcik, D (School of Geography and Environment (University of Oxford), 2010)
In 2000s regulation in the USA and subsequently in Europe responded to the needs of investors and traders, allowing them to take advantage of modern technology, and unleashing competition never before witnessed in the stock exchange industry, with a singular focus on liquidity. By 2010 new exchanges in the USA and Europe proved successful in the battle for liquidity. Essential to their success was the adoption of a simple and efficient business model of two-sided platforms, which contrasts with and threatens the model of diversification and vertical integration embraced by incumbent exchanges. The increased competition and network effects in the industry have been accompanied by its continued concentration in the New York City area in the USA, and emerging dominance of London in Europe, driven primarily by the value of proximity between exchanges and their major customers in terms of computers and human relations. While their iconic incumbent exchanges may suffer, revolution in the stock exchange industry benefits New York City and London as financial centres.